2009
DOI: 10.1242/jeb.031500
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response to low temperature in the freshwater apple snail, Pomacea canaliculata (Gastropoda: Ampullariidae)

Abstract: SUMMARYCold hardiness of the freshwater apple snail, Pomacea canaliculata, varies seasonally. We investigated lethal factors and physiological changes arising from exposure of P. canaliculata to low temperatures. Snails did not survive freezing. The supercooling point of cold-acclimated (cold tolerant) snails (-6.6±0.8°C) did not differ significantly from that of non-acclimated ones (-7.1±1.5°C) under laboratory conditions. Furthermore, snails died even under more moderately low temperatures approaching 0°C. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 27 publications
(31 reference statements)
1
35
1
Order By: Relevance
“…In coincidence, the increase in weight in P. insularum after 10 days at 35 1C was smaller than that in the range 20-30 1C despite the fact that the ingestion rates showed no differences between these temperatures (Gettys et al, 2008). P. canaliculata from temperate Japan (331N) are able to develop cold hardiness before winter Wada and Matsukura, 2007) but unable to tolerate freezing (Matsukura et al, 2009). Recent molecular studies (Hayes et al, 2008) indicate that Asian P. canaliculata populations are the result of multiple introductions from northern Buenos Aires Province (34-351S) where minimum air temperatures in winter are only 2 1C higher than in our study area (371S).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…In coincidence, the increase in weight in P. insularum after 10 days at 35 1C was smaller than that in the range 20-30 1C despite the fact that the ingestion rates showed no differences between these temperatures (Gettys et al, 2008). P. canaliculata from temperate Japan (331N) are able to develop cold hardiness before winter Wada and Matsukura, 2007) but unable to tolerate freezing (Matsukura et al, 2009). Recent molecular studies (Hayes et al, 2008) indicate that Asian P. canaliculata populations are the result of multiple introductions from northern Buenos Aires Province (34-351S) where minimum air temperatures in winter are only 2 1C higher than in our study area (371S).…”
Section: Discussioncontrasting
confidence: 49%
“…The similar latitudes of these Japanese populations and those from the region of origin suggest that cold hardiness could have developed in the native range. P. canaliculata is not usually exposed to subzero temperatures, neither in its southernmost natural populations (our study) nor in the Japanese paddy fields (where snails seek shelter under rice straw; (Matsukura et al, 2009)), which may explain the lack of freezing tolerance reported for Japanese populations.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It is known that the most sensitive to the action of copper are embryos and larvae of fish [22][23][24][25][26]. In connection with this material, developing embryos, pre-larvae, larvae and carp fry were used in research (Cyprinus carpio, L).…”
Section: Resultsmentioning
confidence: 99%
“…Golden apple snails (Pomacea canaliculata) were obtained from the Gapyeong Golden Apple Snail Farm (http://www.gpwoolunge.co.kr/), and a stock population was maintained in aquariums with dechlorinated tap water (water temperature: 25°C ± 1°C; L16:D8) (Matsukura et al, 2009;Takeichi et al, 2007). The behaviors of test organisms were observed in aquariums (30 cm × 30 cm) filled with water to a depth of 15 cm and with a 3 cm sediment layer at four different temperatures (15°C, 20°C, 25°C, and 30°C; L16:D8).…”
Section: Test Organisms and Behavioral Observationsmentioning
confidence: 99%